Mapping common territory—mapping other territory - Deeg, Max (Acta Orientalia Vilnensia, 2007)
Cardiff UniversityThis paper addresses the different functions of the construction of religious, i.e. sacred, space depending on whether such a construction is done in and for its own cultural sphere or whether it is done in and from a cultural context positioned outside the constructed space. This is demonstrated by two case studies of pilgrimage narratives. The first one concentrates on South-Asian culture (Kaśmīr, Nepal) in which two religious traditions (Buddhism, Hinduism) coexisted and constructed sacred space by either the same narratives or by similar but sufficiently different narratives to explain why these places were there and why they were sacred. The other example discusses the approach of culturally different and locally distant Chinese Buddhism towards Buddhist India, where it becomes clear that one of the functions of constructing space by description was to show that the places already known from a textual tradition, the Buddhist one, really existed.